Catalytic combustion performances, kinetics, reaction mechanisms and gas emissions of Lentinus edodes. (March 2020) - Zou, Huihuang; Li, Weixin; Liu, Jingyong; Buyukada, Musa; Evrendilek, Fatih
Graphical abstract: Highlights: How catalysts affect LEP and LES combustion mechanisms and emissions were explored. CaO increased Ea of 9.04 and 22.16 kJ/mol for LEP and LES based on OFW. CaO significantly reduced NO/NO2 emission between 400 and 600 °C. Fe2 O3 enhanced the SO2 emission from 200 to 400 °C and 600 to 850 °C. Thermodynamic equilibrium simulations of ash mineral transformations were studied. Abstract: This study aimed to quantify the catalytic effects of CaO, Fe2 O3, and their blend on the Lentinus edodes stipe (LES) and pileus (LEP) combustion performances, kinetics and emissions in bioenergy generation. Apparent activation energy ( Ea ) of LES and LEP increased with CaO, decreased with Fe2 O3 and differed with their blend. The catalysts mainly affected the maximum intensity of volatiles combustion and partly the fixed carbon combustion. CaO, Fe2 O3, and their blend decreased the release intensity of NOx from the LES combustion. Fe2 O3 increased SO2 emission, while CaO, and the blend narrowed the emission temperature to the range of 200 to 450 °C. Kinetic triplets were estimated via the integral master-plots methods, and the best-fit reaction for the three sub-stages were obtained coupled with the model-free models. Our study provides a reference for the catalyzed biomass combustion in terms of pollution control, bioenergy generation, optimal design of incinerator, and industrial-scale application.